What Do They Learn When They Learn Legal Ethics? - Christine Parker (Legal Education Review)
This paper will discuss incorporating the teaching of legal ethics into the first year undergraduate program of the law degree. Teaching legal ethics in law schools is a subject that has generated renewed interest in recent years. In 2000, the Council of Australian Law Deans endorsed the recommendation of the Australian Law Reform Commission (ALRC), that the development of a deep appreciation of ethical standards and professional responsibility be one of the main aims of university legal education in Australia.3 There is little discussion by the ALRC in its report as to what is meant by ethical standards, and how this “deep appreciation of ethical standards and professional responsibility” should be taught.